Pseudo-nitzschia simulans sp. nov. (Bacillariophyceae), the first domoic acid producer from Chinese waters - Yang, Li; Chun, Xiu Huang; Guo, Shuang Xu; Nina, Lundholm; Sing, Tung Teng; Haiyan, Wu; Zhijun, Tan (Elsevier Ltd., 2017)
The genus Pseudo-nitzschia has attracted attention because of production of the toxin, domoic acid (DA), causing Amnesic Shellfish Poisoning (ASP). Pseudo-nitzschia blooms occur frequently in Chinese coastal waters, and DA has been detected in several marine organisms, but so far no Pseudo-nitzschia strains from Chinese waters have been shown to produce DA. In this study, monoclonal Pseudo-nitzschia strains were established from Chinese coastal waters and examined using light microscopy, electron microscopy and molecular markers. Five strains, sharing distinct morphological and molecular features differentiating them from other Pseudo-nitzschia species, represent a new species, Pseudo-nitzschia simulans sp. nov. Morphologically, the taxon belongs to the P. pseudodelicatissima group, cells possessing a central nodule and each stria comprising one row of poroids. The new species is characterized by the poroid structure, which typically comprises two sectors, each sector located near opposite margins of the poroid. The production of DA was examined by liquid chromatography tandem mass spectrometry (LC–MS/MS) analyses of cells in stationary growth phase. Domoic acid was detected in one of the five strains, with concentrations around 1.05–1.54 fg cell1. This is the first toxigenic diatom species reported from Chinese waters.